Penentuan Prioritas Pemeliharaan Jalan Berbasis Kondisi Permukaan dan Pengambilan Keputusan Multikriteria Menggunakan Metode SDI dan AHP - Dea Ananda Putri; Anwar Efendy; M. Khalis Ilmi (Institut Teknologi Garut, 2026)
Roads are one of the transportation infrastructures that require maintenance according to the level of damage and handling priority. This study aims to assess surface conditions and determine the priority order for maintenance on the Kyai Ahmad Dahlan Road section, West Lombok Regency, by integrating the Surface Distress Index (SDI) and Analytical Hierarchy Process (AHP) methods. A field survey was conducted along 2.2 km of road, divided into 22 segments, each 100 meters long. The SDI method was used to assess surface damage based on cracks, potholes, and rutting, while AHP was used to assign weights to the criteria of SDI, traffic volume, land use, and road width. The analysis results show that SDI values ranged from 35 to 330, with road conditions varying from good to severely damaged. Low values indicate minor damage, while high values indicate the dominance of cracks, potholes, and deformation requiring serious treatment. The most critical segments were found at STA. 0+800–0+900, STA. 0+900–1+000, STA. 1+100–1+200, STA. 1+200–1+300, STA. 1+300–1+400, and STA. 1+500–1+600, with SDI values above 300. The AHP weighting produced an SDI weight of 0.6057, traffic volume of 0.2318, land use of 0.1104, and road width of 0.0521, with a Consistency Ratio of 0.0899, indicating that consistency was achieved. Based on the weighted assessment results, Segment 10 obtained a priority score of 0.9053 and ranked first, Segment 9 obtained a score of 0.9036 and ranked second, while Segment 14 obtained a score of 0.8755 and ranked third. Therefore, these three segments were designated as the main maintenance priorities. These findings confirm that the combination of SDI and AHP methods can produce a more accurate and comprehensive determination of road maintenance priorities.